2003
DOI: 10.1097/01.asn.0000070071.57901.b3
|View full text |Cite
|
Sign up to set email alerts
|

Is a Single Time Point C-Reactive Protein Predictive of Outcome in Peritoneal Dialysis Patients?

Abstract: Abstract. C-reactive protein is the prototype marker of inflammation and has been shown to predict mortality in hemodialysis patients. However, it remains uncertain as to whether a single C-reactive protein level has similar prognostic significance in peritoneal dialysis patients. A single high-sensitivity C-reactive protein (hs-CRP) level was measured in 246 continuous ambulatory peritoneal dialysis patients without active infections at study baseline together with indices of dialysis adequacy, echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
131
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 42 publications
13
131
1
5
Order By: Relevance
“…Our study reconfirmed that factors like age, serum CRP (31) and serum albumin levels (32) are determinants of survival. Although hypoalbuminaemia may reflect a high inflammatory status that determines outcome (6,7), high peritoneal losses are locally regulated by cytokines like IL-6 and do not correlate with the systematic condition.…”
Section: Discussionsupporting
confidence: 79%
“…Our study reconfirmed that factors like age, serum CRP (31) and serum albumin levels (32) are determinants of survival. Although hypoalbuminaemia may reflect a high inflammatory status that determines outcome (6,7), high peritoneal losses are locally regulated by cytokines like IL-6 and do not correlate with the systematic condition.…”
Section: Discussionsupporting
confidence: 79%
“…Patients with obvious clinical inflammation or with temporary vascular catheters presented high CRP levels, demonstrating that uremic patients may show persistent inflammatory activity for multiple reasons. Although this was not a cohort study aiming to evaluate prognostic factors, the finding of increased CRP in patients who eventually died supports previous studies that demonstrated the prognostic power of inflammation markers (24,25). Nevertheless, the albumin levels or nutritional evaluation of patients with higher inflammatory activity did not differ from those observed in the others.…”
Section: Discussionsupporting
confidence: 82%
“…It is interesting to note that CRP levels after the change of the water purification system correlated closely with the previous CRP levels, suggesting that the patients present a pattern of inflammatory activity dependent on other factors. This fact has been emphasized before, making this protein useful as a prognostic tool, even after single isolated measurements (24,25,35,36), despite a high intra-individual variation (37).…”
Section: Discussionmentioning
confidence: 95%
“…Determination of CRP levels is currently recommended by the American Heart Association in all patients at a risk of CVD (15). Also, the decrease in RRF is connected to a stronger inflammatory response in peritoneal dialysis patients with higher concentrations of CRP (16)(17)(18). In our study, CRP was not different between the patients having RRF or not.…”
Section: Discussionmentioning
confidence: 46%
“…A modified PET using 4.25% glucose dialysate was performed and the value of the dialysate-to-plasma creatinine ratio at 4 h was calculated as previously reported (18). The patients were grouped as high (high+high average) and low (low+low average) transporters according to modified PET test.…”
Section: Peritoneal Equilibration Test (Pet) and Assessment Of Dialysmentioning
confidence: 99%